The Criticism of Land Procurement Law to Improve Landowners Welfare in Indonesia - Fifik Wiryani; Mokhammad Najih (Faculty of Law, Sriwijaya University, Indonesia, 2021)
This study is to conduct a juridical analysis of the implications of Law No. 2 of 2012 on Land Procurement for Development for the Public Interest to improve the welfare of landowners after the release of land rights. The focus of the study is on the arrangement of indemnity from the aspects: assessors, indemnity assessment, and deliberation on the determination of indemnity. The research approach uses normative juridical, with secondary data sourced from primary legal materials and secondary legal materials from March to July 2020. The data was analysed using content analysis combined with prescriptive analysis. As a result, this research proposes the arrangement of compensation in the Law on Land Procurement for the Development of the Public Interest. These arrangements are included the material determination of assessors, the value of compensation, deliberationof the determination of compensation, and the custody of compensation (consignment) in the Law on Land Procurement which is inconsistent with the principles and principles of land procurement that should be as the basis and guidelines for the formulation of norms.